Code Switching in Youtube Content Life About Life in Japan - Maulidyawan Danendra; Nuria Haristiani; Susi Widianti (Universitas Tidar, 2022)
This research discusses about the code switching about life in Japan in YouTube content. This research aims to describe the types of code switching and the factors behind the speech. The occurrence of code switching in Youtube content seen from the speakers or users, especially if the speech is spoken by mixed-blood speakers, Japanese learners, and native Japanese speakers that learning Indonesian. Researcher uses the theories of code switching types to describe the variety of code switching sentences and factors that cause code switching to describe the cause of utterance. The results of this research indicate that the most widely used type of code switching is code switching in which speakers insert two codes from another language to the target language with more than one sentence of speech. In terms of the factors causing the occurrence of speech, each speaker shifts the code more when the topic of conversation changes into another discussion.